Inflammatory Bowel Disease and Thrombosis: A National Inpatient Sample Study - Cohen, Jessica B.; Comer, Diane M.; Yabes, Jonathan G.; Ragni, Margaret V. (TH Open, 2020)
Introduction Thrombosis is more common in inflammatory bowel disease (IBD) patients than the general population, but disease-specific correlates of thrombosis remain unclear.Methods We performed a retrospective analysis of discharge data from the National Inpatient Sample between 2009 and 2014, using International Disease Classification codes to identify IBD and non-IBD patients with or without thrombosis. We used NIS-provided discharge-level weights to reflect prevalence estimates. Categoric variables were analyzed by Rao-Scott Chi-square test, continuous variables by weighted simple linear regression, and covariates associated with thrombosis by weighted multivariable logistic regression.Results Thrombosis prevalence in IBD was significantly greater than in non-IBD, 7.52 versus 4.54%, p < 0.0001. IBD patients with thrombosis were older and more likely to be Caucasian than IBD without thrombosis, each p < 0.001. Thrombosis occurred most commonly in the mesenteric vein. Thrombotic risk factors in IBD include surgery, ports, malignancy, dehydration, malnutrition, and steroids at 53.7, 13.2, 13.1, 12.4, 8.9, and 8.2%, respectively. Those with thrombosis had greater severity of illness, 1.42 versus 0.96; length of stay, 7.7 versus 5.5 days; and mortality, 3.8 versus 1.5%; all p < 0.0001. Adjusting for age and comorbidity, odds ratios for predictors of thrombosis included ports, steroids, malnutrition, and malignancy at 1.73, 1.61, 1.34, and 1.13, respectively, while Asian race, 0.61, was protective, each p < 0.001.Conclusion Thrombosis prevalence is 1.7-fold greater in IBD than non-IBD patients. Adjusting for age and comorbidity, the odds ratio for thrombosis in IBD was 73% higher with ports, 61% higher with steroids, 34% with malnutrition, and 13% with malignancy. Whether long-term anticoagulation would benefit the latter is unknown.
Keywords: inflammatory bowel disease; malignancy; malnutrition; steroids; thrombosis